Placental vascular pathology and increased thrombin generation as mechanisms of disease in obstetrical syndromes - Mastrolia,Salvatore Andrea; Mazor,Moshe; Loverro,Giuseppe; Klaitman,Vered; Erez,Offer (PeerJ PrePrints, 2014)
Obstetrical complications including preeclampsia, fetal growth restriction, preterm labor, preterm prelabor rupture of membranes and fetal demise are all the clinical endpoint of several underlying mechanisms (i.e. infection inflammation, thrombosis, endocrine disorder, immunologic rejection, genetic, and environmental), therefore, they may be regarded as syndromes. Placental vascular pathology and increased thrombin generation were reported in all of these obstetrical syndromes. Moreover, elevated concentrations of thrombin-anti-thrombin III complexes and changes in the coagulation as well as anticoagulation factors can be detected in the maternal circulation prior to the clinical development of the disease in some of these syndromes. In this review, we will assess the changes in the hemostatic system during normal and complicated pregnancy in maternal blood, maternal-fetal interface and amniotic fluid, and describe the contribution of thrombosis and vascular pathology to the development of the great obstetrical syndromes.
Keywords: Coagulation; TAT III complexes; TFPI; Protein Z; Amniotic Fluid; IUGR; PROM; Preeclampsia; Fetal demise; Preterm labor